2019
DOI: 10.1371/journal.pone.0216838
|View full text |Cite
|
Sign up to set email alerts
|

Variant analysis pipeline for accurate detection of genomic variants from transcriptome sequencing data

Abstract: The wealth of information deliverable from transcriptome sequencing (RNA-seq) is significant, however current applications for variant detection still remain a challenge due to the complexity of the transcriptome. Given the ability of RNA-seq to reveal active regions of the genome, detection of RNA-seq SNPs can prove valuable in understanding the phenotypic diversity between populations. Thus, we present a novel computational workflow named VAP (Variant Analysis Pipeline) that takes advantage of multiple RNA-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…After that, detected variants i.e., found in mapping plus SNP calling steps were filtered out to minimize false positive variant calls and considered them as priority SNPs. The priority SNPs were filtered with the set of read characteristics summarized by Adetunji et al [ 10 ] using the GATK VariantFiltration tool. In addition, after GATK VariantFiltration, VCFtools v0.1.13 [ 53 ] were used to further filter out specific variants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After that, detected variants i.e., found in mapping plus SNP calling steps were filtered out to minimize false positive variant calls and considered them as priority SNPs. The priority SNPs were filtered with the set of read characteristics summarized by Adetunji et al [ 10 ] using the GATK VariantFiltration tool. In addition, after GATK VariantFiltration, VCFtools v0.1.13 [ 53 ] were used to further filter out specific variants.…”
Section: Methodsmentioning
confidence: 99%
“…The genome sequencing data obtained either experimentally from the next-generation sequencing (NGS) studies or gleaned from various databases available publicly have made it relatively simple and cheap to mine genetic variation in crop plants using various bioinformatics approaches [ 9 ]. Most of the methods detecting variation are based on sequencing data derived either from whole-genome sequencing (WGS) or whole-exome sequencing (WES) [ 10 , 11 ]. In the last few years, NGS approaches in the form of RNA-seq have been co-opted to provide global insights into the gene expression patterns to understand the genetic networks and metabolic pathways involved in maize responses to heat stress [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that lightweight pseudo alignment improves gene expression estimation and at the same time is computationally more efficient, compared with the standard alignment/counting methods [10]. But if the purpose of analysis is to call genomic variants, then it is still better to map the reads to the genome [11]. Considering this, a workflow should provide both quantification strategies to satisfy users with different research interests.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that lightweight pseudo alignment improves gene expression estimation and reduces computational consumption compared with the standard alignment/counting methods [10]. But if the purpose of analysis is to call variants instead of DEA, then it is still better to map reads to genome to avoid reads mapped to spurious locations on the transcriptome [11]. Considering this, a workflow should provide both quantification strategies to satisfy users with different research interests.…”
Section: Introductionmentioning
confidence: 99%